Prevalence and clinical characteristics of rheumatoid arthritis in Poland: a nationwide study - Bogdan Batko (Termedia Publishing House, 2018)
Introduction There are no reliable data regarding the prevalence of rheumatoid arthritis (RA) in Poland.